The Influence of LED Lighting on Attention and Long-Term Memory - Chung Won Lee; Jin Ho Kim (International Journal of Optics)
The fact that the illuminance of LED lights affects human attention and long-term memory has been verified through various studies, but there are no consistent research results about what level of illuminance is effective. The aims of this study were to systematically verify the effects of LED lighting on attention and long-term memory. The experiment was designed with four illuminance levels—300 lx, 400 lx, 500 lx, and 1,000 lx—as experimental conditions to determine the effects of LED lights on attention and long-term memory. Participants in the experiment were 18 college students. The attention task was performed using a handmade attention measuring instrument. Long-term memory was measured by the word fragment completion (hereinafter, referred to as “WFC”) task on the memory retention volume of the learning task that was learned exactly 24 hours before. Of the total 20 tasks, the ratio of correctly retrieval tasks was used as a dependent variable. As a result, attention showed the highest performance with a mean performance of 19.39 (SD = 3.78) at 1,000 lx. A statistically significant difference was also found between the 1,000 lx and 300  lx conditions (p=0.01). On the contrary, long-term memory showed the highest retrieval rate at an average of 58.06% (SD = 22.57) at 400 lx, and long-term memory performance was better in the order of 500 lx (mean = 48.89, SD = 20.33), 1,000 lx (mean = 45.83, SD = 23.53), and 300 lx (Mean = 43.33, SD = 19.10). Statistically, there was a significant difference between 300 lx and 400 lx (p=0.01), 400 lx and 1,000 lx (p=0.01). Through this study, it was verified that the effects of attention and long-term memory are different according to the illuminance of LED lighting, and these results can be important data to clarify the influence of light on human memory in the future.